ANTIOXIDANT CAPACITY OF CARBOLINE INCLUSION COMPLEXES WITH mβCD y βCD - José Muñoz - Espinoza; Germán Barriga (Journal of the Chilean Chemical Society, 2023)
In the present study, the thermodynamic aspects and reactivity of a compound derived from Carboline (7-hydroxy-1-methyl-2,3,4,9-tetrahydro-1H-βcarboline-3-carboxylic acid) when it forms inclusion complexes with βCD and mβCD were described. For this purpose, computational modeling and tools such as Molecular Docking for obtaining the inclusion complex, Second Order Perturbative Analysis (E2PERT) and ONIOM2 (DFT/PM6) for thermodynamic analysis, interactions and reactivity were employed. As a result, it was obtained that the inclusion complexes are viable and stable in the modeled conditions (gas phase, 1 atm and 298K), but not spontaneous. For the process to be spontaneous and viable, the solvent effect and the desolvation of the hydrophobic cavity of the cyclodextrins were considered. On the other hand, the non-covalent interactions were described from the E2PERT analysis, where Hydrogen interactions are shown as donations and acceptance of Lewis and Non-Lewis orbitals. Finally, the global and local reactivity indices show that the ligand presents antioxidant activity of the SET and HAT type in the presence of the OH∙ radical, increasing this tendency when the compound forms inclusion complexes.